2014
DOI: 10.1063/1.4874735
|View full text |Cite
|
Sign up to set email alerts
|

High-electron-mobility GaN grown on free-standing GaN templates by ammonia-based molecular beam epitaxy

Abstract: The dependence of electron mobility on growth conditions and threading dislocation density (TDD) was studied for n−-GaN layers grown by ammonia-based molecular beam epitaxy. Electron mobility was found to strongly depend on TDD, growth temperature, and Si-doping concentration. Temperature-dependent Hall data were fit to established transport and charge-balance equations. Dislocation scattering was analyzed over a wide range of TDDs (∼2 × 106 cm−2 to ∼2 × 1010 cm−2) on GaN films grown under similar conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 60 publications
4
56
0
Order By: Relevance
“…2 Studies have shown that TDs in GaN are electrically active and detrimental to carrier transport in emission properties of semiconductor heterostructures. [3][4][5][6][7][8] Therefore, there is a strong need to get bulk GaN material for homoepitaxial growth of device structures with low TDD.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies have shown that TDs in GaN are electrically active and detrimental to carrier transport in emission properties of semiconductor heterostructures. [3][4][5][6][7][8] Therefore, there is a strong need to get bulk GaN material for homoepitaxial growth of device structures with low TDD.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison is made to two models: Monte Carlo low-field simulations (Ref 12) and a representative fit through numerous experimentally determined mobility data (Ref 13)All samples have comparable crystal quality, with the Na-flux yielding the highest purity, lowest TDD and lowest x-ray rocking curve width. Its Hall mobility of 1057 ± 53 cm 2 /V·s is near the highest mobility recorded to date, 1265 cm 2 /V·s, for GaN with similar FEC and TDD 15. The HVPE samples are of typical commercial quality and have [C] and [Na] comparable to those of the ammonothermal GaN.…”
mentioning
confidence: 82%
“…Crystal quality was characterized by high resolution x-ray diffraction (HRXRD) and measuring the full width at half maximum (FWHM) of the omega rocking curve (ω-XRC) for the on-axis (0002) and off-axis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Bragg plans using a nominal spot size of 10 mm x 1 mm. Impurity concentrations for the ammonothermal samples were measured using secondary ion mass spectrometry (SIMS) using a Physical Electronics 6650 Dynamic SIMS.…”
Section: Methodsmentioning
confidence: 99%
“…According to Matthiessen's rule, the electron mobility is expressed as 1=l total ¼ P i 1=l i , where l total and l i are the total electron mobility and the electron mobility limited by each scattering process, respectively. For the calculation, expressions for the scattering-limited electron mobilities are taken from the following references: ionized impurity, 20 neutral impurity, 21 dislocation, 22 polar optical phonon, 20 acoustic deformation potential, 20 and piezoelectric scattering. 21 We assumed that the effects of other scatterings, such as non-polar optical phonon scattering, are negligible on electron mobility.…”
Section: à3mentioning
confidence: 99%